L2 Learning and academic self-concept: The role of dimensional comparisons - Möller, Jens; Arens, Katrin; Niepel, Christoph (Studies in Second Language Learning and Teaching, 2025)
An expanding literature has explored the impact of second language (L2) self-concept on language achievement and motivation. This review adopts a psychological lens to examine L2 self-concept, beginning with an outline of prominent theoretical frameworks: situated expectancy‐value theory; Shavelson et al.’s (1976) hierarchical, multidimensional model of self-concept; and the integrated Marsh/Shavelson model (Marsh et al., 1988). Building on these foundations, we introduce Marsh’s (1986) internal/external (I/E) frame of reference model, which posits that, within domains such as mathematics or verbal subjects, achievement and academic self-concept are positively correlated, whereas achievement in one domain relates negatively to self-concept in a different domain. Originally confined to mathematics and a single verbal subject in the firstlanguage (L1), the I/E model has been extended to additional disciplines, including L2, through dimensional comparison theory (DCT; Möller & Marsh, 2013). Central to this paper is a synthesis of findings from a recent meta-analysis investigating I/E effects that incorporate measures of L2 achievement and self-concept. Results demonstrate that higher L2 achievement bolsters L2 self-concept while simultaneously diminishing self-concepts in math, physics, biology, and L1; conversely, accomplishments in those other fields exert negative influences on L2 self-concept. We conclude by discussing both theoretical insights and practical applications of self-concept research for language education generally, and L2 instruction specifically.